A "turn-on" fluorescent probe based on BODIPY dyes for highly selective detection of fluoride ions. (June 2021) - Chen, Xi; Liu, Yu-Cong; Bai, Jiang; Fang, Hao; Wu, Fang-Ying; Xiao, Qiang
Abstract: In the present paper, a novel difluoroboron dipyrromethene-based (BODIPY) fluorescent probe with a conjugated hydrazone group, named BDBH, was developed for the detection of F − with high selectivity and sensitivity. After addition of tetrabutylammonium fluoride (TBAF) into a BDBH solution, the fluorescence was "turned on", which displayed an 80-fold increasement of emission intensity. The wavelengths of excitation and emission were 518 nm and 613 nm respectively, which were free from the background interference. The titration of 1 H NMR (Nuclear Magnetic Resonance) indicated that the interaction involved hydrogen-bonding formation between the acidic H of –NH–CO group and F − at low concentration and deprotonation of N–H group at increasing concentration of fluoride. The theoretical calculations verified that once F − interacted with BDBH, the planarity and conjugation of BDBH enhanced, which resulted in a strong fluorescence emission at 613 nm. Furthermore, confocal fluorescence images of BDBH-incubated HeLa cells verified its potential application as an "off-on" sensor to monitor F− in living cells. Graphical abstract: A BODIPY-based fluorescence probe for fluoride detecting named BDBH was developed. It exhibited high selectivity and sensitivity for F − over other reactive anions, such as Cl −, Br −, I −, NO3 −, AcO −, H2 PO4 −, and HSO4 − . Preliminary application of BDBH in living cells fluorescence imaging was further verified its usage as an "Off-On" sensor to monitor F − . Image 1 Highlights: The first reported OFF-ON Fluorescent probe based on BODIPY dyes for F‾ detection through hydrogen-bond interaction. High selectivity and sensitivity, quick response to F‾. Biocompatible probe for detection of F‾ in living cells.